Peran Budaya Banjar dalam Meningkatkan Kinerja dan Keunggulan Bersaing melalui Kewirausahaan Islami dan Strategi (Studi pada Industri Kecil Menengah Batu Mulia/Permata di Martapura Kalimantan Selatan) - Hastin Umi Anisah; Ubud Salim; Made Sudarma; Djumahir - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The aim of this study is to study the relationship between Banjarese culture, Islamic entrepreneurship and strategy, performance, and competitive advantage on small and medium enterprises (SMEs) which produce gem and jewelry stones. The design of this research is mixed methods, where the primary approach is quantitative one and supported by qualitative approach to improve the study. Target population of this research is SME’s Gem and Jewelry Stone products in Martapura. Sample was taken during the quantitative phase using stratified random sampling. Meanwhile, the data were collected by distributing questionnaires which involving 112 respondents. Qualitative approach from Miles-Huberman Model was applied by involving 5 key informants. Whereas quantitative data were processed using structural equation modeling. The research findings show that Banjarese cultures have not yet significantly influenced to the both performance and competitive advantage of the SMEs. On the other hand, the Banjarese culture has improved the SEMs’ performance and competitive advantage through Islamic entrepreneurship and strategy. It means that the implementation of Islamic entrepreneurship in business activities which have done by owner and manager in SME’s Gem and Jewelry Stone product can improve the performance and competitive advantage.Keywords: Banjarese culture, Islamic Entrepreneurship, Strategy, Performance, Competitive advantage, SME’s.